Penerapan Model Pembelajaran Kooperatif Tipe Student Facilitator And Explaining terhadap Hasil Belajar Matematika Siswa - Yufitri Yanto; Ratna Juwita (Jurnal Pendidikan Matematika:Judika Education, 2018)
This study aims to determine the completeness of mathematics learning outcomes of VIII grade students of SMP Negeri B. Srikaton in the academic year 2017/2018 after applying the Student Facilitator and Explaining (SFaE) cooperative learning model. This type of research is experimental, with the design used is pre-test and post-test group design. The population in this study were all eighth grade students of SMP Negeri B. Srikaton, totaling 258 students. One class was randomly sampled, namely class VIII.6 totaling 37 students as an experimental class. The research results obtained by the final score data analysis using t-test. The average score of learning outcomes in mathematics is 81.57. Based on the results of data analysis with a significant level α = 0.05 obtained tcount = 6.41 and ttable = 1.69 because tcount> ttable. Conclusions, that the Implementation of Student Facilitator and Explaining (SFaE) Cooperative Learning Models on Mathematics Learning Outcomes of Class VIII Students of State Junior High School B. Srikaton for the Academic Year 2017/2018 is completed significantly. Keywords: Learning Outcomes, Student Facilitator and Explaining (SFaE) Type of Cooperative learning model.